A voz que se inscreve em Um Beijo dado mais tarde, de Maria Gabriela Llansol - Cláudia Pedrosa Soares (2015)
This thesis investigates the voice in Maria Gabriela Llansol's 'Um beijo dado mais tarde'. The concept of voice is taken from Llansol's texts and is discussed within the contexts of: literary theory, alongside Roland Barthes' notions of 'biographeme' and 'grain of the voice,' as well as Maurice Blanchot's 'parole commençant' of philosophy, relating to the notion of writing by Jacques Derrida, Gilles Deleuze, and Giorgio Agamben; and of Lacanian psychoanalytic theory, especially the notions of 'originary writing,' 'invocatory drive,' and 'voice-object.' Then, I differentiate the voice of the novel from the voice that writes the subject's desire, and finally I define the notion of (in)sonorous voice as it is articulated to desire